Psychophysiological effects of traditional cycling, virtual reality-enhanced cycling, and passive virtual reality exposure in young adults: A controlled within-subject study - Saad A. Alhammad; Abdulmajeed Y. Alhozaimi; Abdulrahman A. Kateeb; Abdulrhman S. Alghamdi; Maha F. Algabbani; Fahad S. Algarni; Mohammed Alrashidi; Mohammed A. Almeshari; Ayedh Alahmari; Shahad M. Almohsen; Khalid S. Alwadeai (PLoS ONE, 2026)
Background Virtual reality (VR) offers a promising tool to enhance engagement in physical activity, but the independent and combined effects of VR on physiological and psychological responses remain underexplored in young adults. Aim To compare acute psychophysiological responses to traditional cycling, VR-enhanced cycling, and passive VR exposure (VR-noEx) in healthy young adults. Methods In this randomized, counterbalanced within-subject study, 60 healthy university students aged 18 years or older completed three 10-minute sessions with 10-minute seated rest between conditions: (1) traditional cycling, (2) cycling with VR, and (3) VR-noEx (VR with no exercise). Outcome measures included self-efficacy, enjoyment, perceived exertion, heart rate (HR), systolic and diastolic blood pressure (SBP, DBP), and respiratory rate (RR). Data were analyzed using repeated-measures ANOVA with post-hoc Bonferroni corrections, and effect sizes were calculated (Cohen’s d). Results Both cycling conditions significantly increased HR (33–35 bpm), SBP (14–17 mmHg), and RR (5.8–6.5 breaths/min) compared to rest (all p < .001), with no significant differences between VR cycling and traditional cycling. VR-noEx did not significantly alter HR or BP relative to rest. VR cycling produced higher self-efficacy and enjoyment than other conditions (p < .05), with small-to-moderate effects and comparable cardiovascular activation. Conclusion VR-enhanced cycling improves self-efficacy and enjoyment without reducing cardiovascular activation, whereas passive VR alone does not confer exercise benefits, suggesting VR-assisted exercise enhances positive psychological responses relevant to physical activity engagement.